Optimizing Government Workforce Performance: A Study of Employee Engagement, Organizational Commitment, and Knowledge Sharing - Mulyana, Deddy; Ahman, Eeng; Sojanah, Janah; Santoso, Budi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The organization must preserve balance by establishing mutually beneficial relationships with its employees, who are its most valuable assets. Several essential aspects are required to maintain this equilibrium, including organizational commitment, employee engagement, and information exchange. We use social exchange theory to investigate the effects of commitment, knowledge sharing, and employee engagement on civil servant performance outcomes (ASN). This study uses a cross-sectional design and includes 115 civil servants from Tasikmalaya. Data analysis utilizes Stata/MP 17.0 for descriptive, bivariable, and multivariable analyses. The research findings indicate a positive impact of employee engagement, affective and normative commitment, and knowledge sharing on ASN performance. However, the negative effect of tenure exceeding five years and continuance commitment on ASN performance is negative. These findings illustrate that while employees are generally expected to have high organizational commitment, continuous commitment to material benefits may be detrimental. The results serve as a basis for discussion among researchers to conduct further longitudinal studies for more accurate conclusions.